Analysis of the Pressure Gradients According to Capsule Flow Mechanism - Ulusarslan, Deniz (WILEY-V C H VERLAG GMBH, 2012)
This study investigated the experimental coefficient in similar to the mathematical correlation for the pressure gradient of spherical capsule train flow according to flow regimes. The investigation was carried out in the 1.2?x?104?
Keywords: flow regime; hydraulic pipelining; pressure gradient; spherical capsule train; SPHERICAL CAPSULES; PIPELINE FLOW; SINGLE CYLINDRICAL; HORIZONTAL PIPES; POLYMER ADDITION; VERTICAL TUBE; TRANSPORT; WATER; DROPS; TRAIN; Chemistry; Science & Technology - Other Topics; Materials Science